2008
DOI: 10.1021/la7024044
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydrodynamics:  The Intrinsic Flow Boundary Condition on Smooth Surfaces

Abstract: A dynamic surface force apparatus is used to determine the intrinsic flow boundary condition of two simple liquids, water and dodecane, on various smooth surfaces. We demonstrate the impact of experimental errors and data analysis on the accuracy of slip length determination. In all systems investigated, the dissipation is described by a well-defined boundary condition accounting for a whole range of separation, film thickness, and shear rate. A no-slip boundary condition is found in all wetting situations. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 32 publications
1
102
0
Order By: Relevance
“…Nearly all of the first reports, and a few of the recent ones, suggested that if slip occurred it was only on nonwetted surfaces (Churaev et al 1984;Blake 1990;Baudry et al 2001;Tretheway and Meinhart 2002;Cottin-Bizonne et al 2008;Maali et al 2008). However, the occurrence of slip was also shown for partially or totally wettable surfaces (Pit et al 2000;Craig et al 2001;Bonaccurso et al 2002;Sun et al 2002;Zhu and Granick 2004;Joseph and Tabeling 2005;Tallon 2007, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nearly all of the first reports, and a few of the recent ones, suggested that if slip occurred it was only on nonwetted surfaces (Churaev et al 1984;Blake 1990;Baudry et al 2001;Tretheway and Meinhart 2002;Cottin-Bizonne et al 2008;Maali et al 2008). However, the occurrence of slip was also shown for partially or totally wettable surfaces (Pit et al 2000;Craig et al 2001;Bonaccurso et al 2002;Sun et al 2002;Zhu and Granick 2004;Joseph and Tabeling 2005;Tallon 2007, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…It is accepted that surface wettability (Pit et al 2000;Bonaccurso et al 2002;Choi et al 2003;Qian et al 2005;Cottin-Bizonne et al 2008;Maali et al 2008), surface roughness (Zhu and Granick 2002;Bonaccurso et al 2003;Truesdell et al 2006;Vinogradova and Yakubov 2006), and super hydrophobicity (Bhushan et al 2009) influence the interaction between liquid and solid at the interface. Thus, the boundary condition necessary for describing the flow of liquid on a solid must be adapted to such situations.…”
Section: Introductionmentioning
confidence: 99%
“…For glycerin displacing silicone oil in capillary tubes, Fermigier and Jenffer 11 estimated l s to be less than 10 nm, consistent with newer and more accurate measurements. 12 This means that a diffuse-interface simulation, in order to achieve the sharp-interface limit, would have to use a comparable ⑀ value. To capture the interfacial profile and hence the interfacial tension accurately, the grid size needs to be at least as small as ⑀.…”
Section: Introductionmentioning
confidence: 99%
“…1). All the typical length scales (particle radius, wall pattern length, and particle-wall gap) considered here are on the order of micrometers, sufficiently large to describe the fluid as a continuum obeying the Navier-Stokes equations [8,9,10,11,12] with no slippage at the solid wall [13,14,15,16,17,18,19]. Our model corresponds to the real case of sufficiently deep grooves where it can be safely assumed perfect-slip at the liquid-gas interface, see e.g.…”
Section: Introductionmentioning
confidence: 99%